An Improved Cr-EA-IRMS Method for the Effective Determination of the Hydrogen Isotopes in Coal Samples - Li, Hongwei; Feng, Lianjun (Frontiers in Chemistry, 2022)
Hydrogen isotope analysis of coal is an important tool in the geochemical analysis of coal. The traditional method of hydrogen isotope analysis of coal requires the oxidation of organic matter bound hydrogen in coal to water by an oxidizing agent and then its reduction to hydrogen by a reducing agent. This method is time-consuming and laborious, and makes it difficult to cope with the rapid detection of large numbers of samples. The recent development of continuous flow IRMS systems (CF-IRMS) has solved the problem of inefficient analysis, but does not guarantee the quantitative conversion of organic bound H to H2, resulting in inaccurate measured hydrogen isotope values. In this study, for the hydrogen isotope analysis of coal, an alternative continuous flow system (Cr-EA-IRMS) was used to achieve high precision hydrogen isotope measurements of coal samples by filling a quartz reaction tube with Cr. The results obtained by this method (−121.3 ± 1.1‰) for the reference material (GBW11104) are consistent with those obtained by the conventional method (−121.4 ± 0.6‰). Using this method, hydrogen isotope measurements for a variety of imported coals revealed significant differences in the hydrogen isotopes of coals from different coal producing regions including Russia, South East Asia, and Australia. Therefore, the use of hydrogen isotope testing analysis of coal could be a potential means of tracing the origin of coal.